1972
DOI: 10.1002/ar.1091720109
|View full text |Cite
|
Sign up to set email alerts
|

A radiographic and histologic study of bone in the active and hibernating bat (Myotis lucifugus)

Abstract: A radiographic and histologic study of bat bones showed that there is a progressive loss of bone tissue during hibernation and abrupt reversal at arousal. Enhanced osteolysis accounted for the bone loss; osteoclasia was not observed.Increasing evidence strongly indicates that the parafollicular cells (light cells, C cells) of the thyroid gland synthesize calcitonin, the bone resorption inhibiting hormone (Pearse, '66; Matsuzawa and Kurosumi, '67; Ericson, '68). Although the importance of calcitonin in mammali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
31
0

Year Published

1972
1972
2004
2004

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 21 publications
5
31
0
Order By: Relevance
“…This contrasts with both clinical systems of unloading and, more intriguingly, with the other natural disuse systems examined to date (hibernating mammals) in which bone remodelling is evident. For example, bone loss has been described in hibernating bats (Myotis lucifugus; Whalen et al, 1971), ground squirrels (Spermophilus undulatus; Mayer and Bernick, 1959) and hamsters (Cricetus cricetus; Kayser and Frank, 1963). In bats, much of the bone loss has been attributed to enhanced osteolysis (Whalen et al, 1971).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This contrasts with both clinical systems of unloading and, more intriguingly, with the other natural disuse systems examined to date (hibernating mammals) in which bone remodelling is evident. For example, bone loss has been described in hibernating bats (Myotis lucifugus; Whalen et al, 1971), ground squirrels (Spermophilus undulatus; Mayer and Bernick, 1959) and hamsters (Cricetus cricetus; Kayser and Frank, 1963). In bats, much of the bone loss has been attributed to enhanced osteolysis (Whalen et al, 1971).…”
Section: Discussionmentioning
confidence: 99%
“…Although overall locomotor performance has never been measured in a hibernator, it is likely to parallel the deficit in isolated muscle performance and thereby reduce the demands on the skeletal system until the muscle regains its prehibernation performance. Hibernation also induces loss of bone in bats (Whalen et al, 1971), hamsters (Kayser and Frank 1963) and squirrels (Mayer and Bernick, 1959). In light of the empirically determined difference in muscle performance between emerging hibernators and aestivators, it seems possible that, in contrast to hibernators, aestivating frogs may preserve long bone size and strength in order to withstand the forces associated with jumping upon emergence.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is feasible that the metabolic depression and associated metabolic recycling that is fundamental to dormancy may help defend skeletal tissues from the effects of disuse. Early studies suggested that small hibernating mammals such as bats, ground squirrels and hamsters might experience bone loss during hibernation (Kayser and Frank, 1963;Mayer and Bernick, 1959;Whalen et al, 1972). However, more recent data from hibernating S. lateralis squirrels indicate that bone strength and stiffness are unaffected by winter inactivity (Utz et al, 2009).…”
Section: Disuse-induced Osteoporosismentioning
confidence: 99%